Konseling Kelompok Teknik Symbolic Modelling untuk Meningkatkan Kecerdasan Emosional Siswa Kejuruan; Efektifkah? - Apriliana, I Putu Agus; Nalle, Andriani P. (Indonesian Journal of Educational Counseling, 2025)
Students with good emotional intelligence can recognize emotions, manage emotions, motivate themselves, recognize other people's emotions, and build good relationships at school. Efforts to increase these skills by school counselor can be facilitated through group counseling with symbolic modeling strategies. Therefore, this study aims to analyze the effectiveness of symbolic modeling techniques in group counseling to increase students' emotional intelligence in vocational schools. A total of 16 students were involved using purposive random sampling techniques. Data was collected using an emotional intelligence scale 37-item. The data analysis technique uses the Wilcoxon test with the GraphPad Prism 8 application. The results show that there is a significant difference in students' emotional intelligence scores after being given treatment. On the other hand, the control group experienced an increase in scores but it was not that significant compared to the experimental group. There were significant differences in scores between the experimental group and the control group. These findings confirm that providing group counseling services using symbolic modeling techniques is effective in increasing students' emotional intelligence in vocational schools. The implications of these findings for professional guidance & counseling services in vocational schools in intervening of group settings on students' emotional intelligence.